Thailand's provincial electricity authority (PEA): A structural equation model of factors determining customer satisfaction - Choaknumkij, Karn; Fongsuwan, Wanno (My University, 2015)
Under the Association of Southeast Asian Nations Economic Community Blueprint 2015, energy security was stated as a top priority. The 10 member community is projected to have a combined gross domestic product of US$ 1.9 trillion by 2020, making this economic block the eighth-largest economy worldwide. With the community's energy consumption rising at a projected 4.4% per year, Thailand with its 67 million people is a key player in both terms of power production, consumption and distribution and at the center of this is the Provisional Electricity Authority which has expanded electricity supply to 73 Thai provinces, covering 510,000 km2 while servicing 99% of the country's total area and villages. Given the critical importance of the PEA to both Thailand and the region, the researchers undertook a study to examine the variables affecting this organization's capability to serve this vital regional sector. Examining both service quality and electronic customer management systems via structural equation modeling, the study determined that there was a direct effect on customer satisfaction by these factors in power generation and distribution within the Kingdom. Given the rising importance of global energy "Smart grid" systems, the study furthermore opened up this area as follow-on to the present research.
Keywords: ASEAN; Customer satisfaction; Electronic customer relationship management; Servicequality; Thailand